Islamophobia in an American studies approach as seen in Donald Trump’s speech documentary videos - Kasiyarno Kasiyarno; Didik Murwantono (Universitas Islam Sultan Agung, 2022)
Donald Trump’s rhetoric in his campaign was markedly different, his speeches on Islamophobia and anti-immigrant rhetoric became a big issue. Trump used the rhetoric of fear to induce his followers against Muslims and immigrants by linking to both groups with the terrorism issue. This article has aims to analyse Trump’s speeches for protecting American people surrounded by the terror threat through an American studies framework. This research was under descriptively qualitative research supported by an interdisciplinary approach of American Studies. Theory of Conservatism and theory of Discursive Psychology were used to analyse American experiences of Islamophobia as seen from Donald Trump’s speeches of documentary videos as the primary data. The completion of this research shows that American conservatives in the era of Donald Trump were strongly enough and the discourse psychological approach was designed to persuade. The discursive approach also allows for an understanding of how American identity, history, and values are both invoked and constructed. It is like American identity of conservatives who are proud of their nationality of Americans.